Prospective multiparametric CMR characterization and MicroRNA profiling of anthracycline cardiotoxicity: A pilot translational study. (December 2022) - Harries, Iwan; Biglino, Giovanni; Ford, Kerrie; Nelson, Martin; Rego, Gui; Srivastava, Prashant; Williams, Matthew; Berlot, Bostjan; De Garate, Estefania; Baritussio, Anna; Liang, Kate; Baquedano, Mai; et al.
Highlights: LVEF partially recovers six months after anthracycline in the majority of patients. Baseline CMR derived MAPSE is associated with poor recovery of LVEF six months after completion of anthracycline. Baseline circulating levels of miRNA-181-5p and miRNA-221-3p associated with poor recovery of LVEF six months after completion of anthracycline. Multiple, significant temporal changes identified by CMR, echocardiography and biomarkers in response to anthracycline. Abstract: Background: Anthracycline cardiotoxicity is a significant clinical challenge. Biomarkers to improve risk stratification and identify early cardiac injury are required. Objectives: The purpose of this pilot study was to prospectively characterize anthracycline cardiotoxicity using cardiovascular magnetic resonance (CMR), echocardiography and MicroRNAs (MiRNAs), and identify baseline predictors of LVEF recovery. Methods: Twenty-four patients (age 56 range 18–75 years; 42 % female) with haematological malignancy scheduled to receive anthracycline chemotherapy (median dose 272 mg/m 2 doxorubicin equivalent) were recruited and evaluated at three timepoints (baseline, completion of chemotherapy, and 6 months after completion of chemotherapy) with multiparametric 1.5 T CMR, echocardiography and circulating miRNAs sequencing. Results: Seventeen complete datasets were obtained. CMR left ventricular ejection fraction (LVEF) fell significantly between baseline and completion of chemotherapy (61 ± 3 vs 53 ± 3 %, p < 0.001), before recovering significantly at 6-month follow-up (55 ± 3 %, p = 0.018). Similar results were observed for 3D echocardiography-derived LVEF and CMR-derived longitudinal, circumferential and radial feature-tracking strain. Patients were divided into tertiles according to LVEF recovery (poor recovery, partial recovery, good recovery). CMR-derived mitral annular plane systolic excursion (MAPSE) was significantly different at baseline in patients exhibiting poor LVEF recovery (11.7 ± 1.5 mm) in comparison to partial recovery (13.7 ± 2.7 mm), and good recovery (15.7 ± 3.1 mm; p = 0.028). Furthermore, baseline miRNA-181-5p and miRNA-221-3p expression were significantly higher in this group. T2 mapping increased significantly on completion of chemotherapy compared to baseline (54.0 ± 4.6 to 57.8 ± 4.9 ms, p = 0.001), but was not predictive of LVEF recovery. No changes to LV mass, extracellular volume fraction, T1 mapping or late gadolinium enhancement were observed. Conclusions: Baseline CMR-derived MAPSE, circulating miRNA-181-5p, and miRNA-221-3p were associated with poor recovery of LVEF 6 months after completion of anthracycline chemotherapy, suggesting their potential predictive role in this context. T2 mapping increased significantly on completion of chemotherapy but was not predictive of LVEF recovery.